2022
DOI: 10.3390/foods11203230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Five Different Lactic Acid Bacteria on Bioactive Components and Volatile Compounds of Oat

Abstract: In this research, oats were fermented with Lactobacillus plantarum, Lactobacillus acidophilus, Lactobacillus casei, Lactobacillus bulgaricus and Streptococcus thermophilus for 48 h at 37 °C. The purpose of this work was to compare the growth capacities of the five lactic acid bacteria (LAB) in the oat matrix and the effects of fermentation on the contents of the bioactive components of oat, such as β-glucan, polyphenols, flavonoids and volatile compounds at different time (0, 4, 8, 12, 24, 36 and 48 h). After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The bread containing the sourdough fermented by LAB and yeast (S4B) had the highest total odor intensity and vinegar sourness. Main VOCs detected in oat sourdoughs and breads belonged to alcohols, aldehydes, and carboxylic acids classes, as also found in other studies on fermented oat and wheat sourdough bread ( De Luca et al, 2021 ; He et al, 2022 ). In sourdoughs fermented by L. brevis IC9 (S1) and by the consortium of LAB and yeast (S4) ethanol and acetic acid were the most abundant.…”
Section: Discussionsupporting
confidence: 85%
“…The bread containing the sourdough fermented by LAB and yeast (S4B) had the highest total odor intensity and vinegar sourness. Main VOCs detected in oat sourdoughs and breads belonged to alcohols, aldehydes, and carboxylic acids classes, as also found in other studies on fermented oat and wheat sourdough bread ( De Luca et al, 2021 ; He et al, 2022 ). In sourdoughs fermented by L. brevis IC9 (S1) and by the consortium of LAB and yeast (S4) ethanol and acetic acid were the most abundant.…”
Section: Discussionsupporting
confidence: 85%
“…Other compounds like hexanal (grassy, green) and (E)-2-hexenal (green) are usually linked to the apples (immobilization carrier) and were identified only in the products fortified with immobilized cells [ 69 ]. However, their presence could also be a result of microbial metabolism and their inhibitory effect against Saccharomyces and Aspergillus species has been previously well documented [ 70 , 71 , 72 , 73 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, a study by He and colleagues [ 82 ] reported a decrease in TPC during fermentation. Oats were fermented with Lb.…”
Section: Effects Of Fermentation On the Chemical Composition Of Oatsmentioning
confidence: 99%